The evaluation of efficiency in the various leg-kicking techniques in scuba diving - Rejman, M.; Siermonstowski, P.; Ogrodnik, B. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The aim of this study was to analyse the various techniques of the underwater leg-kicking in terms of their efficiency, defined as an effective and economical use of their surfaces to achieve maximal speed. We hypothesised that identification of the factors determining the efficiency of various leg-kicking provides basis for choosing the optimal techniques adequate to the utilitarian aims undertaken by scuba divers.